Child vulnerability and HIV/AIDS in sub-Saharan Africa: what we know and what can be done - Gillespie, Stuart; Norman, Amy; Finley, Betsy (International Food Policy Research Institute, 2005)
Among the many devastating consequences of the AIDS epidemic in sub-Saharan Africa, the rapidly growing orphan population demands particular attention. Today, over 12 million children in the region have been orphaned by AIDS, a population that is increasing by the minute as HIV-positive parents become ill and die from AIDS (UNAIDS/UNICEF/USAID 2004). Millions more children are living with chronically ill parents, and about three million are themselves infected with the virus. Estimates differ, but some organizations predict a tripling of orphan numbers in the next five years...In this paper, [f]irst, we briefly review the evidence for the different aspects of vulnerability experienced by children affected by HIV and AIDS...Second, we draw upon the small but growing body of evidence of what works in addressing child vulnerability in the context of HIV and AIDS in order to generate some key principles for policy and programming. We conclude by highlighting research priorities.